3(3x - 1) + 2(3 - x) = 0 <=>
9x-3+6-2x=0 <=>
7x+3=0 <=> x=-3/7
2007-01-16 07:04:17
·
answer #1
·
answered by Anonymous
·
3⤊
0⤋
Solve 3(3x - 1) + 2(3 - x) = 0
First: eliminate parenthesis > multiply the outer terms with the terms in the parenthesis...
3(3x) - 3(1) + 2(3) - 2x = 0
9x - 3 + 6 - 2x = 0
Sec: combine "like" terms...
9x - 2x - 3 + 6 = 0
7x + 3 = 0
Third: subtract 3 from both sides...
7x + 3 - 3 = 0 - 3
7x = -3
*Solve for "x" by isolating it on one side-divide both sides by 6...
7x/7 = -3/7
x = -3/7
2007-01-16 07:59:59
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Solve 3(3x - 1) + 2(3 - x) = 0?
9x-9 +6 -2x =0
7x = 3
x=3/7
2007-01-16 07:04:21
·
answer #3
·
answered by ironduke8159 7
·
0⤊
1⤋
Very simple:
3(3x-1) + 2(3-x) = 0
9x - 3 + 6 - 2x = 0
7x + 3 = 0 (-3 from both sides)
7x = -3 (divide both sides by 7)
x = -3/7 or as a decimal -0.428571429
Easy!
Good luck!
Lorna
2007-01-16 07:05:42
·
answer #4
·
answered by Anonymous
·
2⤊
0⤋
Use distributive property:
9x-3+6-2x=0
Combine like terms:
7x+3=0
Subtract 3 from both sides:
7x=-3
Divide 7 from both sides:
x=-3/7
Check:
3(3(-3/7)-1)+2(3-(-3/7))=0
3(-9/7-7/7)+2(21/7+3/7)=0
3(-16/7)+2(24/7)=0
-48/7+48/7=0
0=0
I hope this helps!
2007-01-16 07:33:06
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
the solution is:
9x-3+6-2x=0
7x=-3
x=-3/7
2007-01-16 07:08:18
·
answer #6
·
answered by HIMANSHU A 1
·
2⤊
0⤋
3(3x-1) + 2(3-x) = 0
9x-3 + 6-2X = 0
7x-3=0
x= 3 /7
x = 0.43
i could be wrong
2007-01-16 07:06:04
·
answer #7
·
answered by JENNIFER C 2
·
1⤊
0⤋
no longer positive if it truly is eliminating, yet right it truly is how i'd do it... you want to get y in words of x, which signifies that you're taking one equation and sparkling up it so that you've 'y' on in reality one part, like this: -4x-15=5y (divide both part by 5) -4/5x -3 = y With y on my own on fringe of the equation you've decreased y's fee to a formula of 'x'. with a view to substitute that in the 2d equation and sparkling up. for the reason that y is a similar as -4/5x -3 then we substitute as follows 2y = 11-5x 2(-4/5x -3) = 11-5x -8/5x - 6 = 11 - 5x -8/5x = 17 - 5x -17/5x = 17 5/17 * 17/5x = 5/17 * 17 -x = 5 or x = -5 Now that you've the cost for X you could plug that into both unique equation and get the cost of 'y'. 2y = 11 - 5(5) 2y = -14 y = -7
2016-11-24 21:34:11
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
3(3x-1) + 2(3-x)=0
9x-3+6-2x=0
7x+3=0
7x=-3
x=-3/7
2007-01-16 07:06:26
·
answer #9
·
answered by Jyse 6
·
2⤊
0⤋
9x-3+6-2x=0
7x+3=0
7x=-3
x=-3/7
2007-01-16 07:07:09
·
answer #10
·
answered by Dave aka Spider Monkey 7
·
2⤊
0⤋